SERVICE QUALITY, PROMOTION AND AFTER SALES SERVICE EFFECT ON HONDA MOTORCYCLE CUSTOMER SATISFACTION AT ASTRA MOTOR CENTER JAKARTA - Rafsanjani, Sherva (International Journal of Science, Engineering, and Information Technology, 2025)
Companies in the motorcycle business exist to meet the public's driving needs, leading to intense competition among similar companies in presenting product excellence to capture consumer attention. This competition is unavoidable for Honda Astra Motor Center Jakarta , which must continuously strive to achieve its desired market share through strategic business policies and excellent service aimed at customer satisfaction.To face this intense competition, companies need to conduct intensive promotional activities using various promotional media such as print, electronic, and outdoor media. However, to increase product sales, companies must be able to strictly and selectively select the advertising media they will use for their own promotional activities. The purpose of this study is to determine the effect of service quality, promotion, and after-sales service on customer satisfaction, service quality on customer satisfaction, promotion on customer satisfaction, and how after-sales service conditions affect customer satisfaction. The testing process was carried out using several methods: validity testing, reliability testing, multicollinearity testing, heteroscedasticity testing, normality testing, and multiple linear regression analysis. The results of the Effect of Service Quality, Promotion and After Sales Service on Consumer Satisfaction Simultaneously at the level of significance below 0.05, service quality, promotion, and after sales service have a simultaneous effect on customer/consumer satisfaction. For the Partial Effect of Service Quality on Consumer Satisfaction through questionnaires distributed to respondents, most respondents stated that they agree that service quality has a positive effect on customer/consumer satisfaction. For the Partial Effect of Promotion on Consumer Satisfaction, it states that promotion has a significant effect on customer/consumer satisfaction. In the Partial Effect of After Sales Service on Consumer Satisfaction, most respondents stated that they did not agree that after sales service has a positive effect but has a negative effect on customer/consumer satisfaction.